2022
DOI: 10.1093/jjco/hyac061
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of distinct genomic features reveals frequent somatic AHNAK and PTEN mutations predominantly in primary malignant melanoma presenting in the ureter

Abstract: Background Primary malignant melanoma of the ureter is extremely rare. Genetic variants to the increased risk of developing the disease have not yet been investigated. Methods Tumour mutation profiling for primary malignant melanoma of the ureter was performed by whole-exome sequencing. Immunohistochemistry was performed to verify histopathological features and the variants of predisposing genes and driver mutation genes. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…The overall mutation rate was 7%, and the mutation types were deep deletions and diploidy. According to the literature, alterations in ANK3 and type I collagen may increase the risk of developing ureteral primary malignant melanoma ( 25 ). The ectopic expression of ANK3 significantly increased E-calcineurin expression and restricted the progression of papillary thyroid carcinoma (PTC), which suggests that ANK3 has an anti-cancer action in PTC development, and serves as the inert maintainer of PTC ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall mutation rate was 7%, and the mutation types were deep deletions and diploidy. According to the literature, alterations in ANK3 and type I collagen may increase the risk of developing ureteral primary malignant melanoma ( 25 ). The ectopic expression of ANK3 significantly increased E-calcineurin expression and restricted the progression of papillary thyroid carcinoma (PTC), which suggests that ANK3 has an anti-cancer action in PTC development, and serves as the inert maintainer of PTC ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al. reported that AHNAK expression was downregulated in primary malignant melanoma PMM in ureteral tissue compared to paracancerous ureteral tissue ( 59 ). Another study noted that AHNAK expression was significantly downregulated in melanoma and correlated with poor prognosis, and that knockdown of AHNAK in primary melanocytes resulted in reduced expression of E-calcineurin ( 60 ).…”
Section: Relationship Between Ahnak Family and Tumor Developmentmentioning
confidence: 99%
“…Ureter-originating malignant melanoma is considered to be extremely uncommon [ 77 ]. Genetic variants associated with the increased disease risk have not yet been investigated.…”
Section: Main Findings Of the Literature (Review) Questmentioning
confidence: 99%